IMPLEMENTATION OF MINI SOLAR POWER PLANTS IN RESIDENTIAL HOUSES - Xakimov Temurbek (Лучшие интеллектуальные исследования, 2024)
Abstract. This article is about residential applications of mini solar power plants. Ways to solve the problems and shortcomings of the solar power plant were seen. In addition, modern technologies used in mini solar power plants and their calculations are presented.